Autoregulation of Human Jejunal Mucosal Perfusion During Cardiopulmonary Bypass - Nygren, Andreas; Thorén, Anders; Houltz, Erik; Ricksten, Sven-Erik (Anesthesia and analgesia, 2006)
Animal studies have suggested that autoregulation of intestinal blood flow is severely impaired during cardiopulmonary bypass (CPB). We investigated the jejunal mucosal capacity to autoregulate perfusion during nonpulsatile CPB (34°C) in 10 patients undergoing elective cardiac surgery. Changes in mean arterial blood pressure (MAP) were induced by altering the CPB flow rate randomly for periods of 3 min from 2.4 L/min/m2 to either 1.8 or 3.0 L/min/m2. Jejunal mucosal perfusion (JMP) was continuously recorded by laser Doppler flowmetry. A typical pattern of flow motion (vasomotion) was recorded in all patients during CPB. Variations in CPB flow rates caused no significant changes in mean JMP, jejunal mucosal hematocrit, or red blood cell velocity within a range of MAP from 50 ± 15 to 74 ± 16 mm Hg. The vasomotion frequency and amplitude was positively correlated with CPB flow rate. IV injections of prostacyclin (10 μg, Flolan®) blunted vasomotion and increased JMP from 192 ± 53 to 277 ± 70 (P < 0.05) perfusion units despite a reduction in MAP from 59 ± 12 to 45 ± 10 mm Hg (P < 0.05). Prostacyclin-induced vasodilation resulted in loss of mucosal autoregulation (pressure-dependent perfusion). We conclude that autoregulation of intestinal mucosal perfusion is maintained during CPB in humans.